2009
DOI: 10.1063/1.3187794
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of low-frequency oscillations in the human cardiovascular system

Abstract: We investigate synchronization between the low-frequency oscillations of heart rate and blood pressure having in humans a basic frequency close to 0.1 Hz. A method is proposed for quantitative estimation of synchronization between these oscillating processes based on calculation of relative time of phase synchronization of oscillations. It is shown that healthy subjects exhibit on average substantially longer epochs of internal synchronization between the low-frequency oscillations in heart rate and blood pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
1
17

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(106 citation statements)
references
References 35 publications
4
84
1
17
Order By: Relevance
“…These indices can assess cardiac autonomic regulation but not peripheral blood flow. In our previous papers, we have proposed an original method for the assessment of cardiovascular autonomic control based on synchronization between the 0.1-Hz rhythms in heart rate (HR) and photoplethysmogram (PPG) (21). The quality of 0.1-Hz rhythms synchronization was found to be higher in healthy subjects than in patients with cardiovascular disease (22).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These indices can assess cardiac autonomic regulation but not peripheral blood flow. In our previous papers, we have proposed an original method for the assessment of cardiovascular autonomic control based on synchronization between the 0.1-Hz rhythms in heart rate (HR) and photoplethysmogram (PPG) (21). The quality of 0.1-Hz rhythms synchronization was found to be higher in healthy subjects than in patients with cardiovascular disease (22).…”
Section: Methodsmentioning
confidence: 99%
“…Very-lowfrequency range of HRV was not included in our analysis to avoid questionable results, because we registered short-time ECG records (2). To estimate synchronization between the 0.1-Hz rhythms in HR and PPG, we used the method proposed by us recently (21). Index S defines the relative time of synchronization between the 0.1-Hz rhythms considered.…”
Section: Signal Processingmentioning
confidence: 99%
“…To estimate synchronization between the 0.1-Hz rhythms in HR and PPG we used the method proposed by us recently (10,19). Index S defines the relative time of synchronization between the considered 0.1-Hz rhythms.…”
Section: Hrv and Ppgmentioning
confidence: 99%
“…The 0.1-Hz rhythm in HR is an estimate of combined vagal and β-sympathetic activity (17), whereas the 0.1-Hz rhythm in peripheral BP is an estimate of α-sympathetic activity (18). It has been found that 0.1-Hz rhythms can be synchronized between themselves (10,12,19). From physiological viewpoint, the synchronization of 0.1-Hz rhythms is the result of adequate functional interaction of CVS parts.…”
Section: Introductionmentioning
confidence: 99%
“…Было показано, что эти контуры демонстрируют длительные (десятки характерных периодов) участки фазовой синхронизации [31]. Был предложен метод расчета индекса S для оценки удельного времени синхронного поведения этих контуров [11,28] и показана значимость индекса S для медицинской диагностики патологий сердечно-сосудистой системы, выбора медикаментозной терапии инфаркта миокарда и гипертонической болезни, прогноза ослож-нений и риска смерти пациентов кардиологического профиля [16].…”
Section: Introductionunclassified